An Analytical Evaluation of Dr. Amjad Ali Bhatti’s Role in Literary Translation - Bibi , Dr. Raheela; BiBi , Dr.Zeenat; Ali, Dr.Saba; Afridi, Dr. Muhammad Nasir; Waheed , Sameeqa; bibi , Saira; Sobia, (Al-Qanṭara, 2025)
Dr. Amjad Ali Bhatti’s contributions as a translator represent a significant intersection of scholarship, cultural mediation, and literary enrichment in Pakistan. Trained at the doctoral level in Punjabi literature, he has translated over forty works from English, Punjabi, and Hindi into Urdu, ranging from classical Sufi poetry to European philosophy, modern fiction, and critical theory. His translations maintain fidelity to the original texts while ensuring linguistic clarity, stylistic precision, and cultural contextualization for Urdu readers. Notable projects include Urdu renditions of Punjabi Sufi poetry by Baba Farid, Shah Hussain, Sultan Bahu, Bulleh Shah, Hashim Shah and Waris Shah as well as translations of Rousseau, Shakespeare, and Charlie Chaplin. Beyond individual publications, Dr. Bhatti has played a formative role in establishing Translation Studies as an academic discipline in Pakistani universities, including UOG, NUST, and IIUI, contributing to pedagogical frameworks, scholarly discourse, and cross-cultural intellectual exchange. His work exemplifies translation as an interpretive and creative practice rather than mere linguistic substitution, bridging historical, spiritual, and literary knowledge for contemporary audiences. Collectively, his translations and academic leadership underscore the capacity of Urdu translation to preserve cultural heritage, promote intercultural dialogue, and democratize access to global literature and thought.